POTIVS MORI QUAM FOEDARI - Belda Navarro, Cristobal (Imafronte, 1994)
The title of this paper (potius mori quam foedari) recalls the device engraved on the arms of Juan de Guevara which emblazon the main entrance to his house, completed in 1694, in the town of Lorca. The aim of the paper is to relate the dweller’s personality to the decorative elements of the façade and to the possibility of analysing it in the context of the literature on emblems and devices that were so in vogue in the Baroque period. The hypothesis of this paper is based on the concept of personal honour and on the prevalent values of a society in which the distinctive traits of class and lineage were not alien.